Angular distribution of particles sputtered from a copper target by 5‐keV Kr ions: Experiment and simulation study. (28th June 2021) - Afkir, Ahmed; Ait El Fqih, Mohammed; Jadoual, Lamia; Shulga, Vladimir; Kaddouri, Abdelilah
Abstract : Angular distributions of atoms sputtered from a copper target under 5‐keV Kr + bombardment at normal incidence were simultaneously and independently studied by experiments and computer simulation. The sputtered particles are collected on a Mylar™ foil placed around the target. Deposited particles on the substrate were analyzed by optical transmission spectroscopy. The surface roughness of the irradiated target was studied by atomic force microscopy, surface profilometry, and scanning electron microscopy. The experimental results were compared with the simulated angular distributions (programs OKSANA, SDTrimSP, and SRIM) and were found to be in reasonable agreement. In all cases, the angular distribution of sputtered particles showed an over‐cosine shape, which may be associated with noncompensated scattering of ejected particles by surface atoms when exiting the target. The results obtained are compared with the data from the literature.